Psychedelic-Assisted Psychotherapy: Clarifying the Role of the ‘Psychotherapy’ - Jerotic, Stefan; Čolović, Olga; Marić, Nadja (Medical Research, 2026)
Psychedelic-assisted psychotherapy (PAP) is emerging as a novel intervention for major psychiatric disorders, most notably major depressive disorder (MDD) and post-traumatic stress disorder (PTSD). While psychotherapy is widely regarded as a core element of PAP its precise role remains poorly defined. This narrative review traces the development of PAP within contemporary Western psychiatry, outlines the therapeutic framework of preparation, dosing, and integration, and synthesizes findings from recent high-impact randomized controlled trials with psilocybin and MDMA. The primary purpose of this review is to clarify the role of psychotherapy in PAP. Despite methodological rigor, studies differ substantially in their therapeutic orientation, degree of manualization, and therapist involvement, yet all report significant clinical benefit. Some evidence points to the fact that treatment outcomes may not depend on the number of psychotherapy hours, raising questions about whether psychotherapy functions as an active ingredient, a facilitative context, or a safeguard. In light of these inconsistencies, we discuss novel phenomenological accounts of change in PAP, which propose that psychedelics exert therapeutic effects by altering “existential feelings,” with psychotherapy primarily serving to stabilize and integrate these shifts. Current evidence highlights both the promise of PAP and the unresolved uncertainty regarding its psychotherapeutic components. Clarifying these issues will require trials that explicitly address psychotherapeutic variables, as well as the establishment of standardized protocols, ethical safeguards, and licensure pathways for practitioners.